Play in Children with Autism – Parents and Professionals’ Perception - Jovana Đokić; Mirjana Đorđević; Nenad Glumbić; Aleksandra Đurić-Zdravković (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji)
Play is a central activity of childhood that provides children with enjoyment and stimulates the development of creativity. It helps them better understand the world around them, express their emotions, refine motor skills, and develop essential life skills. The aim of this study is to determine whether there is a difference in how parents and professionals perceive the play of children with autism. The sample included parents of children with autism (N = 60) and professionals (N = 60) employed in kindergartens and schools attended by these children. The children's ages ranged from four years and eight months to nine years (AS = 7.70; SD = 1.03). To assess play performance, the My Child’s Play – Parent Questionnaire (MCP; Schneider & Rosenblum, 2014) was used. The results showed statistically significant differences in play perception between parents and professionals in the subscales of Interpersonal Relationships and Social Participation (p < 0.05), Executive Functions (p < 0.05), and Play Choices and Preferences (p < 0.05). Parents perceived their child’s engagement in play more positively, including their ability to join play, adapt to new play partners, maintain focus, stay organized, persist, and overcome frustrating situations that may arise during play.